PAVINGISASI PUSAT KOTA DENPASAR: KAJIAN FUNGSIONAL DAN ESTETIKA - Syamsul Alam Paturusi (Bumi Lestari Journal of Environment, 2010)
The government of Denpasar City has organized Gajahmada Street and Kamboja Street through the project of pavement which has cost a lot. Physical, functional, role, quality and visual degradations as well as the decrease in the shopping activities and the damaged shapes of the buildings have led to this policy. To overcome such problems, the space quality has been improved with reference to the scale of pedestrians. Having been conducted for about one year, it is time to evaluate the project. The objectives are to identify whether the project has been successful as expected and whether esthetic and function have been given priority. The approach applied was physical trace observation (Zeisel, 1995) which was combined with the analysis of secondary data (the document containing the planning and comparative study of the area of pedestrians of La Rambla in Barcelona) which was then analyzed and interpreted. The results of the field and data analysis show that the plans which had been made to support the project of pavement of the two corridors was not in accordance with what had been expected. As the illustrations, the change of the traffic current was not carried out and the capacity of and accessibility to the parking center were still problems. These were the principle issues which should be paid attention to if the two corridors were expected to be the ones for the pedestrian. The other thing to which attention was not paid to was the attractiveness of the corridors (something to see, something to buy and something to do). In addition, the pedestrian’s motivation was not explored either. These are all seen at La Rambla, Barcelona. The conclusion which can be withdrawn from this study is that what has been planned for Gajahmada Street and Kamboja Street has given more priority to their aesthetics than functions. It is suggested that in the future a deep analysis should be made in the macro planning before every physical planning is made. After that, architectural, technical and aesthetic planning is made.